Integration of Bamboo Forestry into Carbon Markets - King, C.; Lugt, P. van der; Trinh, T.L.; Li, Y. (International Bamboo and Rattan Organisation (INBAR), 2021)
This policy brief provides an introduction to how bamboo forestry projects can be integrated into carbon markets. By explaining how to develop and register bamboo forestry projects for certification in carbon markets, this policy brief aims to support project developers and government actors to gain additional incomes from these projects and integrate bamboo more into national climate strategies.